PENGARUH PEMANFAATAN LINGKUNGAN SEKITAR TERHADAP KETERAMPILAN MENULIS DESKRIPSI SISWA KELAS V SDN 54 - Hendriana, Hesti; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the effect of the utilization of surrounding environment to descripstion writing skills of class V students of West Pontianak 54 Elementary School. The method used is the experimental method, while the form of research used is quasi experimental design with nonequivalent control group design. The population and sample in this study were all five grade students of West Pontianak 54 Elementary School. The data collection tool used was a form essays with 2Â  questions. Based on data analysis, the average post-test results of the experimental class were 72,96 while the average post-test results of the control class were 65,33. The results of the t test are obtained t count of 4,624 and t table Î± = 5% (with dk = 35 + 36 - 2 = 69) of 1,669, which means tcount (4,624)> t table (1,669), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is influence the utilization of surrounding environment to descripstion writing skills in class V of West Pontianak 54 State Elementary School. From the results of the calculation of the effect size (ES) obtained is 0,78(medium criteria). This means that the utilization of surrounding environment learning have a good influence on the descripstion writing skills of class V students of West Pontianak 54 Elementary School.Keywords: Author Description, Surrounding Environment, Writing Skills